"البروتوكول في المنظمات الدولية منظمة الأمم المتحدة انموذج" (Comprehensive Journal of Science, 2025)
Due to the special nature of international organizations, diplomatic relations with them are subject to a special legal regime that differs from diplomatic representation between states, because the diplomatic relationship with the organization is a triangular relationship ( sending state – organization - headquarters state), which entails a different protocol practice than that followed in diplomatic representation between states, because the principle of sovereign equality cannot be applied between states and international organizations, and therefore a relationship cannot be established on the basis of reciprocity, because of the different legal and material nature between states and international organizations, and since the United Nations is the largest international organization so that most of the world's countries have representation in it, where diplomatic missions enjoy a legal system that distinguishes them from diplomatic missions to states, and therefore the diplomatic protocol and protocol followed with permanent and even observer and non-permanent missions in them are of great importance as they are considered the reference on which other international organizations are based with regard to protocol practices in them.
Keywords: Protocol- Governments organizations- diplomatic missions- diplomatic representation.